Quality of Institutions, Credit Markets and Bankruptcy - Christa Hainz (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2005)
The number of firm bankruptcies is surprisingly low in economies with poor institutions. We study a model of bank-firm relationship and show that the bank?s decision to liquidate bad firms has two opposing effects. First, the bank receives a payoff if a firm is liquidated. Second, it loses the rent from incumbent customers that is due to its informational advantage. We show that institutions must improve significantly in order to yield a stable equilibrium in which the optimal number of firms is liquidated. There is also a range where improving institutions may decrease the number of bad firms liquidated.
Keywords: G33; K10; G21; D82; 330; Credit markets; institutions; bank competition; information sharing; bankruptcy; relationship banking